Systematic modeling and symbolically assisted simulation of power systems. - Hiskens, I.A.
Large disturbance behavior of power systems often involves complex interactions between continuous dynamics and discrete events. Such behavior can be captured in a systematic way by a model that consists of differential, switched algebraic and state-reset (DSAR) equations. The paper presents a practical object-oriented approach to implementing the DSAR model. Each component of a system can be modeled autonomously. Connections between components are established by simple algebraic equations. Simulation of the model using numerically robust implicit integration requires the generation of partial derivatives. The object-oriented model structure allows this differentiation to be achieved symbolically without sacrificing simulation speed
Keywords: Continuous dynamics; Differential equations; Differentiation; Discrete events; Large disturbance behavior; Numerically robust implicit integration; Object-oriented approach; Object-oriented model structure; Power systems; State-reset equations; Switched algebraic equations; Symbolically assisted simulation; Systematic modeling